2015
DOI: 10.1016/j.jaci.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 desensitizes β2-adrenergic receptors in human airway epithelial cells through a 15-lipoxygenase/G protein receptor kinase 2 mechanism

Abstract: Background Beta-2 adrenergic receptor (β2AR) agonists are critical treatments for asthma. However, receptor desensitization can lead to loss of therapeutic effects. While desensitization to repeated use of β2 agonists is well studied, Type-2 inflammation could also impact β2AR function. Objective To evaluate the impact of the Type-2 cytokine, IL-13, on β2AR desensitization in human airway epithelial cells (HAECs) and determine whether 15-Lipoxygenase-1 (15LO1) binding with phosphatidylethanolamine binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…We previously reported that IL‐13 augments carbachol‐induced airway narrowing and attenuates β 2 ‐adrenoceptor agonist‐induced airway dilation in human PCLS (Cooper et al , ; Robinett et al , ). Although IL‐13 attenuates β 2 ‐adrenoceptor agonist‐induced airway (Laporte et al , ; Grunstein et al , ; Duan et al , ; Cooper et al , ; Robinett et al , ; Albano et al , ), IL‐13 has little effect on PI3K p110 inhibitor‐induced airway dilation as shown in Figure . We and others have shown that HASM cells derived from fatal asthma donors manifest distinct phenotypes compared to cells derived from non‐asthmatic patients, including cell proliferation (Roth et al , ), enzymatic function (Chambers et al , ; Trian et al , ), receptor signalling and sustained calcium transients consistent with contractility of the muscle (Ma et al , ; Leguillette and Lauzon, ; Chin et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that IL‐13 augments carbachol‐induced airway narrowing and attenuates β 2 ‐adrenoceptor agonist‐induced airway dilation in human PCLS (Cooper et al , ; Robinett et al , ). Although IL‐13 attenuates β 2 ‐adrenoceptor agonist‐induced airway (Laporte et al , ; Grunstein et al , ; Duan et al , ; Cooper et al , ; Robinett et al , ; Albano et al , ), IL‐13 has little effect on PI3K p110 inhibitor‐induced airway dilation as shown in Figure . We and others have shown that HASM cells derived from fatal asthma donors manifest distinct phenotypes compared to cells derived from non‐asthmatic patients, including cell proliferation (Roth et al , ), enzymatic function (Chambers et al , ; Trian et al , ), receptor signalling and sustained calcium transients consistent with contractility of the muscle (Ma et al , ; Leguillette and Lauzon, ; Chin et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory milieu in asthma engenders AHR to contractile agonists and attenuates β 2 agonist‐induced bronchodilation (Cooper et al , ; Albano et al , ; Gupta et al , ). Previously, we showed that exposure to IL‐13 renders airways hyposensitive to β 2 ‐adrenoceptor agonist‐mediated airway dilation but not TAS2 receptor‐mediated airway dilation (Robinett et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model in which asthmatic features persisted for 6 months after cessation of allergen exposure demonstrated that a critical network of feedback and feed forward interactions between epithelial cells and ILC2s is taking place, in which IL‐13 is central and involved in maintaining chronic asthma . In addition, it was shown that IL‐13 desensitizes β2‐adrenergic receptors in human airway epithelial cells , thus offering a potential explanation for the increased AHR.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysates were run on 4-12% gradient SDS-PAGE gels under reducing conditions, as previously described. 29 Western blotting (WB) was performed with primary antibodies against 15LO1 (1:1000 dilution; a gift of Dr Doug Conrad, University of California, San Diego, Calif), CCL26 (1:100 dilution; R&D Systems, Minneapolis, Minn), phosphorylated ERK (pERK; 1:5000 dilution; Sigma, St Louis, Mo), total ERK (tERK; 1:5000 dilution; Sigma), and glyceraldehyde-3-phosphate dehydrogenase (GAPDH; 1:1000 dilution; Novus Biologicals, Littleton, Colo). Densitometric analysis was performed with ImageJ software (National Institutes of Health, Bethesda, Md).…”
Section: Western Blottingmentioning
confidence: 99%